ANALISIS HASIL PORTING DAN POLISHING TERHADAP TORSI SEPEDA MOTOR 150 cm3 : THE ANALYSIS OF PORTING AND POLISHING RESULTS AGAINST MOTORCYCLE TORQUE 150 cm3 - Rizky Fajar Ananda (Jurnal Teknik Mesin, 2024)
The purpose of this study is to investigate the torque results on standard and modified vehicles, presenting torque comparison graphs for standard and modified motorcycle engines. The experimental study used a 150cm3 motorcycle, analyzing the experimental results directly. The study shows the difference in performance, especially torque, across all engine variations at every 500rpm. The study involved porting and polishing modifications to increase engine torque, resulting in a 4.8% increase in torque over standard. The modifications widened the torque range, providing improved performance across a wide range of speeds. The modified motorcycle exhibited faster acceleration, navigating the terrain and heavy traffic with ease. Improved performance at high speeds, stability and temperature maintenance were observed. The porting and polishing modifications had a positive impact on engine torque throughout 6500 to 9000rpm, with 6500 rpm porting A and polishing B displaying optimal results, achieving 14.4Nm of torque, an increase of 0.8Nm over standard conditions.